2023
DOI: 10.3390/brainsci13030461
|View full text |Cite
|
Sign up to set email alerts
|

Exploring a Possible Interplay between Schizophrenia, Oxytocin, and Estrogens: A Narrative Review

Abstract: Schizophrenia is characterized by symptoms of psychosis and sociocognitive deficits. Considering oxytocin’s antipsychotic and prosocial properties, numerous clinical, and preclinical studies have explored the neuropeptide’s therapeutic efficacy. Sex differences in the clinical course of schizophrenia, as well as in oxytocin-mediated behaviors, indicate the involvement of gonadal steroid hormones. The current narrative review aimed to explore empirical evidence on the interplay between schizophrenia psychopatho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 137 publications
0
5
0
Order By: Relevance
“…The fifth and most recent hypothesis suggests a reduction in levels of oxytocin, in comparison to normal values in women with PPD, which was based on previous evidence from non-perinatal samples (29,30). Only one study (26) met the criteria in our search.…”
Section: Two Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…The fifth and most recent hypothesis suggests a reduction in levels of oxytocin, in comparison to normal values in women with PPD, which was based on previous evidence from non-perinatal samples (29,30). Only one study (26) met the criteria in our search.…”
Section: Two Hypothesesmentioning
confidence: 99%
“…Only one study (26) met the criteria in our search. A non-perinatal study (29) found low levels of oxytocin in patients with a first psychotic episode, highlighting that increasing it can lessen alterations of mood and social cognition. Another study (30) reported that during menopause, lower levels of oxytocin in women with schizophrenia are associated with more severe psychiatric symptoms.…”
Section: Two Hypothesesmentioning
confidence: 99%
“…A recent hypothesis regarding schizophrenia suggested that insufficient estrogen and oxytocin levels are upstream etiologies. Moderate increases in these hormones ameliorate the positive and negative symptoms of schizophrenia by attenuating impairments in prepulse inhibition, resulting in the facilitation of emotion recognition and social interaction ( 34 ).…”
Section: Introductionmentioning
confidence: 99%
“…Research suggests that mentalization is linked with specific brain structures and networks, notably the right temporoparietal junction, the right middle temporal gyrus, and the left precuneus [ 29 ]. It has also been hypothesized that there is a reciprocity between sex hormones and social cognition in schizophrenia, where oxytocin, estrogens, and testosterone could have a role [ 30 ], and being exposed to these in fetal life might have an effect on the disorder [ 31 ]. An expanding body of literature has documented various deficits in both cognitive and affective facets of mentalizing in individuals diagnosed with psychosis, and the anomalies within this specific metacognitive domain are responsible for a significant portion of the compromised social functioning and poor social outcomes observed [ 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%